Preschool Teachers’ Attitudes Towards Slovenian as a Second Language (Preučevanje otroške in mladinske književnosti, 2025)
The article presents the attitudes of preschool teachers and preschool teachers’ assistants towards the acquisition of Slovenian as a second language in kindergarten. The results of a survey of 458 preschool teachers and preschool teachers’ assistants from randomly selected kindergartens in Slovenia show that teachers and teaching assistants agree with the statement that a bilingual or multilingual child changes/switches language according to the language of his or her interlocutor in a given situation (M = 3.96, SD = 0.74). The statement that it makes sense to send parents whose first language is not Slovenian recordings of songs or fairy tales in Slovenian so that they can play them to their children at home and thus help the children to learn the Slovenian language more quickly is also rated highly (M = 3.83, SD = 0.93).